2015
DOI: 10.1080/19443994.2014.911119
|View full text |Cite
|
Sign up to set email alerts
|

Magnetised titanium dioxide (TiO2) for water purification: preparation, characterisation and application

Abstract: The study of titanium dioxide (TiO 2 ) as a photocatalyst for water purification has attracted significant attention over the past four decades. However, the separation of photocatalyst from water suspension may be difficult, costly and jeopardize the use of this water treatment technology. Recently, the development and production of magnetised TiO 2 have been achieved to offer a solution for the photocatalyst separation problem. This paper discusses the preparation techniques, characterisation and the applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 140 publications
0
8
0
Order By: Relevance
“…The conversion of bulk titanium dioxide into nanobelts makes it more efficient for the removal of dyes during water cleaning. Titanium dioxide was also coated converted into magnetic material for easy recovery and to facilitate its repetitive usage as a photocatalyst [6]. Titanium dioxide was also coupled with ferrites.…”
Section: Introductionmentioning
confidence: 99%
“…The conversion of bulk titanium dioxide into nanobelts makes it more efficient for the removal of dyes during water cleaning. Titanium dioxide was also coated converted into magnetic material for easy recovery and to facilitate its repetitive usage as a photocatalyst [6]. Titanium dioxide was also coupled with ferrites.…”
Section: Introductionmentioning
confidence: 99%
“…Akvarez et al prepared Fe 3 O 4 /TiO 2 and Fe 3 O 4 /SiO 2 /TiO 2 (referred to as MS-TiO 2 ) nanoparticles and reported that incorporating a silica layer between the Fe 3 O 4 core and photocatalyst shell not only reduced the negative effect of magnetite on the photocatalysis process of TiO 2 but also protected the magnetic core against oxidation, retaining magnetic properties of the nanocomposite and enriching its removal efficiency [28]. Recently, a few publications described the construction of recyclable photocatalytic nanocomposites of Fe 3 O 4 /SiO 2 /TiO 2 with core-shell structure using sol-gel methods [29][30][31][32][33][34]. These studies focused on the nanocomposite's ability to photodegrade various organic pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Among the extensive variety of metal oxide nanomaterials, titanium dioxide nanomaterials (TNMs) (e.g., anatase, rutile, TiO 2 (B) and titanate) have attracted considerable attention because of their unique physicochemical properties compared to the bulk material. TNMs play an important role in various applications such as photocatalytic degradation of organic pollutants [1–2], sensors [3–4], solid oxide fuel cells [5], water purification [6–7], adsorption of radioactive and heavy metal ions [8], as well as antibacterial applications [9]. Their various applications can be divided into “energy” and “environment” related categories.…”
Section: Introductionmentioning
confidence: 99%